Prototipe Kepemimpinan Kiai di Pesantren Modern - Rusdiono Mukri; Abas Mansur Tamam (Jurnal Dirosah Islamiyah, 2021)
This study aims to determine the implementation of the management and leadership of kiai Pondok Modern Darussalam Gontor in order to continue to exist and even become a prototype of leadership and management of modern Islamic boarding schools in Indonesia. The study used descriptive qualitative methods which were carried out by collecting data obtained from documentation, observation and interviews, and supported by literature studies, both from books and journals. The results of the study show that the modernity of Pondok Gontor is seen in the implementation of management which is different from Islamic boarding schools in general. Gontor's management is carried out based on the principles of transparency and accountability as well as togetherness. Pondok Gontor adheres to a collective, democratic, and transformational leadership model. This leadership model is proven to be able to bring about change in every student and teacher to achieve high performance. Through its vision and mission, Pondok Gontor strives to produce strong and solid leaders, leaders who have a noble soul and philosophy of life, correct values and are involved in the totality of life in the boarding with high discipline.